Synthetic Antibody‐Rhamnose Cluster Conjugates Show Potent Complement‐Dependent Cell Killing by Recruiting Natural Antibodies. Issue 16 (21st February 2022) - Ou, Chong; Prabhu, Sunaina Kiran; Zhang, Xiao; Zong, Guanghui; Yang, Qiang; Wang, Lai‐Xi
Abstract: Monoclonal antibodies (mAbs) are one of the most rapidly growing drug classes used for the treatment of cancer, infectious and autoimmune diseases. Complement‐dependent cytotoxicity (CDC) is one of the effector functions for antibodies to deplete target cells. We report here an efficient chemoenzymatic synthesis of structurally well‐defined conjugates of a monoclonal antibody with a rhamnose‐ and an αGal trisaccharide‐cluster to recruit natural anti‐rhamnose and anti‐αGal antibodies, respectively, to enhance the CDC‐dependent targeted cell killing. The synthesis was achieved by using a modular antibody Fc‐glycan remodeling method that includes site‐specific chemoenzymatic Fc‐glycan functionalization and subsequent click conjugation of synthetic rhamnose‐ and αGal trisaccharide‐cluster to provide the respective homogeneous antibody conjugates. Cell‐based assays indicated that the antibody‐rhamnose cluster conjugates could mediate potent CDC activity for targeted cancer cell killing and showed much more potent efficacy than the antibody‐αGal trisaccharide cluster conjugates for CDC effects. Abstract : A highly efficient chemoenzymatic synthesis of homogeneous antibody‐rhamnose and antibody‐αGal cluster conjugates is described. The synthesis was achieved through a modular antibody Fc‐glycan remodeling that includes site‐specific chemoenzymatic Fc‐glycan functionalization and subsequent click conjugation of synthetic rhamnose‐ and αGal trisaccharide clusters. A comparative cell‐based assay indicated that the antibody‐rhamnose cluster conjugates showed potent complement‐dependent targeted cancer cell killing by recruiting natural anti‐rhamnose antibodies.